Les femmes et le comique dans le théâtre du marquis de Sade - Bénédicte Prot (Itinéraires)
This article investigates the place and function of women in Sade’s fictions and focuses specifically on Sade’s theatre. Its aim is to define the role of female characters in three comedies (Le Boudoir, Les Jumelles, Le Misanthrope par amour). The characters in question show Sade’s intentions in his theatre: we contend that Sade is playing with the rules of traditional dramatic art, and that he aims, as a result, at creating a particular comical effect. Sophie, Mme Dolcour, Adélaïde and Julie are not stereotypes but philosophical entities. They reveal how Sade exposes his preoccupations on stage and how he attempts to create a comic based on irony and imagination.